Center problem in the center manifold for quadratic differential systems in R3. (March 2016) - Giné, Jaume; Valls, Claudia
Abstract: Using tools of computer algebra based on the Gröbner basis theory we derive conditions for the existence of a center on a local center manifold for fifteen seven-parameter families of quadratic systems on R 3 . To obtain the results we use modular arithmetics.